Understanding colonial chieftaincy from its final phase: responses to the crisis of an institution in French-ruled West Africa and beyond, 1944–1960 - Keese, Alexander (Africana Studia, 2020)
With the transfers of power in still-colonial sub-Saharan Africa, the epoch of ‘traditional chieftaincy’ seemed to be finally over. The chiefs, frequently regarded by historians and social scientists as a product of the colonial state, appeared to lose all of their authority. Or so it seemed. Fifty years later, we are puzzled by the resilience of chieftaincy in many parts of the African continent. A more profound analysis of chieftaincy in several West African territories under colonial rule shows that also in the late colonial states, the chiefs had their margin of manoeuvre. Those who did not adapt to the wishes and requirements of the local populations, who now had far more political means at their disposal than it had been the case before, lost their position. However, many ‘traditional rulers’ learnt how to play the game, and the 1940s and 1950s were a period in which they acquired the skills to survive after independence. Keywords: chieftaincy, adaptation, decolonization, French West Africa, challenge of authority.